Exploration of the 3D World on the Internet Using Commodity Virtual Reality Devices - Tran, Huy Quang (Auckland University of Technology, 2018)
This thesis describes the development of a graphically interactive and online Virtual Reality (VR) application. Based on keywords provided by users, it automatically retrieves and display stereoscopic contents from the Internet. The system also includes a state-of-the-art feature matching algorithm which can filter stereoscopic contents from “normal” 2D contents. With the main goal of delivering an affordable way of viewing 3D VR contents, the application is designed to be specifically compatible with the low-cost smartphone VR platforms such as Google Cardboard, Google Daydream, and Samsung Gear VR. The experiment results show that the current application prototype is portable, easy-to-use, and effective in retrieving and displaying stereoscopic contents. With this application, users all over the world could easily experience millions of stereoscopic contents on the Internet. It also has a huge potential of becoming a great tool for both VR testing and learning purposes.
Keywords: Virtual reality; Smartphones; Stereoscopic; Internet; Online; 3D images; Unity3D; Google Cardboard